2007
DOI: 10.1007/s11120-007-9157-1
|View full text |Cite
|
Sign up to set email alerts
|

Excitation energy transfer in native and unstacked thylakoid membranes studied by low temperature and ultrafast fluorescence spectroscopy

Abstract: In this work, the transfer of excitation energy was studied in native and cation-depletion induced, unstacked thylakoid membranes of spinach by steady-state and time-resolved fluorescence spectroscopy. Fluorescence emission spectra at 5 K show an increase in photosystem I (PSI) emission upon unstacking, which suggests an increase of its antenna size. Fluorescence excitation measurements at 77 K indicate that the increase of PSI emission upon unstacking is caused both by a direct spillover from the photosystem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
36
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 41 publications
7
36
0
Order By: Relevance
“…Conversely, release of LHCII trimers enhances F680. There are several lines of evidence linking F680 to free LHCII, among which LHCII release from grana cores induced by thylakoid unstacking (van der Weij-de Wit et al 2007), LHCII release from grana margins induced by digitonin treatment of isolated thylakoids (Grieco et al 2015), and also steady-state conditions in which LHCII trimers are overly abundant as compared to photosystem cores (Pantaleoni et al 2009; Ferroni et al 2013). Native LHCII trimers have a strong tendency to aggregate in vitro, leading to the appearance of a new long-wavelength band, F700, also accompanied by a quenching of fluorescence, which could support a role of LHCII aggregates in excess energy dissipation (Mullet et al 1980; Ruban and Horton 1992; Karapetyan 2004; Schaller et al 2011).…”
Section: Question 17: Can the 77 K Fluorescence Emission Bands Be Assmentioning
confidence: 99%
“…Conversely, release of LHCII trimers enhances F680. There are several lines of evidence linking F680 to free LHCII, among which LHCII release from grana cores induced by thylakoid unstacking (van der Weij-de Wit et al 2007), LHCII release from grana margins induced by digitonin treatment of isolated thylakoids (Grieco et al 2015), and also steady-state conditions in which LHCII trimers are overly abundant as compared to photosystem cores (Pantaleoni et al 2009; Ferroni et al 2013). Native LHCII trimers have a strong tendency to aggregate in vitro, leading to the appearance of a new long-wavelength band, F700, also accompanied by a quenching of fluorescence, which could support a role of LHCII aggregates in excess energy dissipation (Mullet et al 1980; Ruban and Horton 1992; Karapetyan 2004; Schaller et al 2011).…”
Section: Question 17: Can the 77 K Fluorescence Emission Bands Be Assmentioning
confidence: 99%
“…Another possibility is that some CFL 250 ps in WT cells originates from the PSI associated with LHCII formed in state 2. This possibility can be excluded, however, because less than 2% of the fluorescence at 665-685 nm is derived from PSI at room temperature (13), and the CFL of PSI fluorescence at those wavelengths is shorter than ∼70 ps (18)(19)(20), a time range that our FLIM system cannot resolve. Taken together, these observations suggest that the CFL 250 ps observed in WT cells indicates phospho-LHCII dissociation, and that FLIM enabled visualization of the spatiotemporal spread of dissociated phospho-LHCII during state 2 transitions in live cells.…”
Section: Chlorophyll Fluorescence Lifetime Of Dissociated Phospho-lhcmentioning
confidence: 99%
“…Although the distribution of the two reaction centres is inhomogeneous in higher plants, PSI and PSII still have a chance to directly interact. The two reaction centres coexist in a flexible nonappressed region 3,4 , and about half of PSIIs exist in stroma thylakoids and grana margins where PSIs also exist 5 . Recently, Järvi et al 6 reported coexistence of PSI and PSII complexes together with light-harvesting complexes (LHCs) in large-pore blue-native polyacrylamide gel electrophoresis (PAGE) from Arabidopsis, suggesting possible interaction between the complexes.…”
mentioning
confidence: 99%